Automatic Lock System for Computer using Bluetooth and Fingerprint Authentication - Wan Ismail, Wan Hazimah (Journal of Computing Technologies and Creative Content, 2020)
Windows Operating System (OS) do have their own authentication policies that provide security to the system. However, these policies do not entirely protect the system from unauthorized user. This is because text-based, password can be easily cracked or stolen by someone else using methods such as brute- force and shoulder surfing. Hence it does not guarantee the safety of the system. This project will focus on developing an automatic locking system for a computer using Bluetooth technology with the fingerprint authentication method. Bluetooth is an open standard specification for a radio frequency (RF) - based, short range wireless technology that is designed to be an inexpensive. Bluetooth technology is suitable for our project because its medium range of communication. To increase the security of our system, we enhance our project by adding fingerprint authentication method. By adding this method, the system only be able to unlock by someone that have registered fingerprint.